Efektivitas Sistem Gudang Fulfillment Shopee terhadap Ketepatan Waktu Pengiriman - Marsekal Muhammad Jamal; Erwin Permana (Jurnal Ekonomi dan Pembangunan Indonesia, 2025)
The fulfillment warehouse system is one of the logistics innovations implemented by e-commerce platforms to enhance operational efficiency and customer satisfaction. Shopee, as one of the largest e-commerce platforms in Indonesia, has introduced the Shopee Fulfillment Center to assist sellers in the storage, packaging, and shipping processes. This study aims to analyze the impact of Shopee’s fulfillment warehouse system on the timeliness of order deliveries. The research employs a descriptive qualitative approach, with data obtained through observation and digital searches. The findings indicate that Shopee’s fulfillment warehouse system is effective in ensuring timely deliveries by optimizing storage, processing, and distribution operations. Through automation technology, optimized warehouse layouts, and real-time tracking system integration, Shopee accelerates order processing times, reduces the risk of delays, and improves delivery accuracy. Additionally, the presence of distribution centers across various regions helps minimize travel distances and speeds up the delivery process to customers. Continuous investment in logistics infrastructure and strategic partnerships with multiple courier services further contribute to supply chain efficiency, ensuring faster and more timely deliveries while enhancing customer satisfaction.